2004
DOI: 10.1007/s00018-004-4214-9
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-?-lactamases: two binding sites for one catalytic metal ion?

Abstract: During the past few years the results from molecular biological, biochemical, chemical, physical and theoretical approaches expanded the knowledge about metallo-beta-lactamases considerably. The main reason for the attracted interest is a persisting medical problem. Bacteria expressing metallo-beta-lactamases can be resistant to treatment with all the known beta-lactam antibiotics, and they are additionally invulnerable to combined treatment with inhibitors for the wider-spread serine-beta-lactamases. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 121 publications
2
100
0
3
Order By: Relevance
“…2, 26,42,43 Similarly, it appears that some MBLs can operate as mononuclear enzymes, while others require two metal ions. 5, 44,45 In contrast, the present study supports a mechanistic model for GpdQ whereby the mononuclear form is inactive and a substrate-and metal-ioninduced fit leads to the formation of a catalytically active binuclear center, providing an intricate regulatory mechanism for enzyme activity ("on-off switch").…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…2, 26,42,43 Similarly, it appears that some MBLs can operate as mononuclear enzymes, while others require two metal ions. 5, 44,45 In contrast, the present study supports a mechanistic model for GpdQ whereby the mononuclear form is inactive and a substrate-and metal-ioninduced fit leads to the formation of a catalytically active binuclear center, providing an intricate regulatory mechanism for enzyme activity ("on-off switch").…”
Section: Resultssupporting
confidence: 72%
“…Furthermore, the catalytic mechanism of GpdQ may also be related to other binuclear metallohydrolases, such as methionine aminopeptidase (MetAP) 2,26,42,43 and metallo--lactamases (MBLs). 5, 44,45 However, MetAP is flexible in that it can operate as either a mononuclear or binuclear hydrolase, with each form having a distinct reaction mechanism. 2, 26,42,43 Similarly, it appears that some MBLs can operate as mononuclear enzymes, while others require two metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the very tight binding of only one of the metal ions in the active site it was suggested that MBLs may only require one Zn(II) for catalysis under physiological conditions, especially since it is estimated that the concentration of free Zn(II) in cells may be in the picomolar range or lower [12]. However, this inter- pretation raises a serious issue in terms of why all known MBLs have two closely spaced metal ion binding sites in their catalytic centres-as already mentioned in a previous report it appears unlikely that such a structural arrangement would be conserved throughout evolution if there was no functional benefit for the enzyme [110].…”
Section: Interactions Between Mbls and Metal Ionsmentioning
confidence: 99%
“…Zinc-bound ␤-lactamases appear to be more stable than their corresponding metal-depleted forms (9), and removal of the metal is known to induce conformational changes (40,46,50). No detailed information on the conformational stability of MBLs has, however, been reported to date (for a brief review of the literature, see under "Discussion").…”
Section: ؊1mentioning
confidence: 99%